ความหลากหลายของโมนิโลไฟต์บริเวณเขาแหลม อุทยานแห่งชาติหมู่เกาะช้าง จังหวัดตราด - ไพฑูรยากุล โศภิษฐา; เทียนหอม อารยา อาจเจริญ; จารุวัฒนพันธ์ ทัศไนย (Thai Journal of Science and Technology, 2019)
Abstract Diversity of monilophytes in Khao Laem area, Mu Ko Chang National Park, Trat province was explored from December 2016 to September 2018. A total of 242 specimens was collected and identified to 54 species in 36 genera and 18 families by using morphological traits. The most representative families in numbers of species found were Pteridaceae 10 species (subfamily Pteridoideae 4 species and subfamily Vittarioideae 6 species) Polypodiaceae 8 species and Hymenophyllaceae 5 species. Regarding the habitats, there were 32 species of terrestrials, 10 species of epiphytes and 3 species of lithophytes. Besides, 9 species could be found in more than one habitats, and some species had a potential to be the locally ornamental plants. Keywords: fern; monilophyte; diversity; Ko Chang